Keterampilan Berpikir Kritis Siswa SMP pada Pembelajaran Materi Konsep Ekosistem Menggunakan Model Inkuiri Dipadu Kooperatif - Bimo Aji Nugroho; Muhammad Zaini; M. Arsyad (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The inquiry learning model is a process of collecting information through experimentation in solving problems. The school environment can be used in a meaningful learning process, instilling knowledge, awareness, positive attitudes and students’ behavior. This study aims to describe the effect of students' critical thinking skills through the use of an integrated cooperative inquiry model. The method used is descriptive method to describe students' critical thinking skills. The research sample was divided into treatment class (VII A and VII B) and control class (VII C). The results showed a good influence on students' critical thinking skills, such as formulating problems, making hypotheses, making observations, and making analyzes, while the activities of making conclusions were classified as quite good criteria.